Primary liver cancer in Georgia: Seven years’ experience following the launch of the Hepatitis C Elimination Program, 2015–2022 - Anna Khoperia; Susan H. Gawel; Jenna Bedrava; Nazibrola Chitadze; Maia Butsashvili; Alan Landay; Geoff A. Beckett; Sophia Surguladze; Konstantine Kazanjan; Vladimer Getia; Maia Tsereteli; Maia Alkhazashvili; et al. (PLoS ONE, 2026)
Hepatitis C virus (HCV) infection is associated with hepatocellular carcinoma (HCC), the predominant form of primary liver cancer (PLC). In 2015, Georgia implemented the HCV Elimination Program to reduce high national prevalence. We analyzed linked national registry data to characterize primary liver cancer cases in Georgia and evaluate the burden and treatment patterns of HCV infection among affected individuals during the national HCV elimination program. Data from the Georgian Cancer Registry (GCR), the national Vital Registration System, and the HCV Elimination Program databases were linked to perform a descriptive analysis of adult PLC cases diagnosed between January 2015-December 2022 and examine trends in HCV infection and treatment among them. Of 1734 reported PLC cases, 72.0% were male with a median age of 63 years (IQR 56–70). Two-thirds presented with stage 3–4 liver cancer and 80.2% were deceased by the end of 2022. Screening for HCV among PLC cases rose from 14.0% in 2015 to 92.8% in 2022. Of 1389 tested, 785 (56.5%) were anti-HCV positive. Of these, 654 (83.3%) were confirmed to be HCV RNA or HCVcAg positive, 472 (72.2%) of which had advanced liver fibrosis or cirrhosis. Among 654 HCV RNA or HCVcAg positive individuals, 495 (75.7%) initiated HCV treatment, with 355 (71.7%) treated more than one year before their PLC diagnosis. Our analysis supports the known association between PLC and HCV infection in Georgia. The high proportion of PLC cases receiving HCV treatment prior to their liver cancer diagnosis highlights the need to establish routine post-treatment follow-up for cirrhotic patients to facilitate earlier detection of PLC and improve outcomes.